Improvement of skeletal muscle performance in ageing by the metabolic modulator Trimetazidine. Issue 4 (5th January 2016) - Ferraro, Elisabetta; Pin, Fabrizio; Gorini, Stefania; Pontecorvo, Laura; Ferri, Alberto; Mollace, Vincenzo; Costelli, Paola; Rosano, Giuseppe
Abstract: Background: The loss of muscle mass (sarcopenia) and the associated reduced muscle strength are key limiting factors for elderly people's quality of life. Improving muscle performance does not necessarily correlate with increasing muscle mass. In fact, particularly in the elderly, the main explanation for muscle weakness is a reduction of muscle quality rather than a loss of muscle mass, and the main goal to be achieved is to increase muscle strength. The effectiveness of Trimetazidine (TMZ) in preventing muscle functional impairment during ageing was assessed in our laboratory. Methods: Aged mice received TMZ or vehicle for 12 consecutive days. Muscle function was evaluated at the end of the treatment by a grip test as well as by an inverted screen test at 0, 5, 7 and 12 days of TMZ treatment. After sacrifice, muscles were stored for myofiber cross‐sectional area assessment and myosin heavy chain expression evaluation by western blotting. Results: Chronic TMZ treatment does not affect the mass of both gastrocnemius and tibialis anterior muscles, while it significantly increases muscle strength. Indeed, both latency to fall and grip force are markedly enhanced in TMZ‐treated versus untreated mice. In addition, TMZ administration results in higher expression of slow myosin heavy chain isoform and increased number of small‐sized myofibers. Conclusions: We report here some data showing that the modulation of skeletal muscle metabolism by TMZ increases muscle strength in aged mice. Reprogramming metabolism might therefore be a strategy worth to be further investigated in view of improving muscle performance in the elderly.